Implikasi Hukum Peningkatan Status Hak Guna Bangunan (HGB) Dan Hak Pakai (HP) Atas Rumah Tinggal Obyek Hak Tanggunganmenjadi Hak Milik Terhadap Kreditur - Arba -; Arief Rahman Hakim; Muhammad Umar; Wiwiek Wahyuningsih; Shinta Andriyani (Jatiswara, 2016)
This research aims to study the legal implications of Status change from the Right to Build and theRight to Use to become the right of ownership over a mortgage object for Creditors. This is a normative-empirical research, i.e. research which is seeking to discover legal values, norms, concepts, its application, and the legalimplications of the status change of the right. This research applies normative and socio-legal approaches. Normative approach itself applies statute, conceptual, and analytical approach. Meanwhile, socio-legal approach itself applies social and economic approach. The legal material resource of the research is literature data which consist of primary, secondary and tertiary legal material, meanwhile the field resource of it are primary and secondary data.Any legal actions or action law will lead to an implication of law or legal consequences. Legal actions or changes or improvement HGB/HP became to HM will lead to abolishment of the land rights and legal status of the land rights into state land, so that all the rights of other parties that are attached to the land rights had previously been removed. For that to holders of HT does not feel disadvantaged, then in the BPN Head Regulation No. 5 of 1998 has been set clearly on the protection of the law and the rights of creditors Mortgage holders.